Modeling of liquid and gas flows in the horizontal layer with evaporation - Lyulin Yuri; Rezanova Ekaterina (EPJ Web of Conferences, 2017)
Mathematical modeling of two-layer flows in the "ethanol-nitrogen" system on the basis of the exact solutions of a special type is carried out. The influence of the gas flow, temperature and Soret effect on the flow patterns and evaporating processes at the interface is investigated. The results of comparison of the experimental and theoretical data are presented; the dependence of the evaporation intensity at interface of the gas flow rate and temperature is studied.